‘STEM belonging’: the association between stereotype vulnerability, COVID-19 stress, general self-efficacy, multidimensional perceived social support, and STEM interest among Physics, Chemistry, and Mathematical Science students - Gulsah Dost (International Journal of Adolescence and Youth, 2024)
This study aimed to develop and validate a theoretical framework elucidating the connections between general self-efficacy (GSE), multidimensional perceived social support (MPSS), STEM interest (SI), stereotype vulnerability (SVS-4), COVID-19 Student Stress (CSSQ), and STEM Belonging (SB) among a diverse group of students in England. An online survey was administered to 290 Mathematics (n = 83, 28.6%), Physics (n = 95, 32.8%), and Chemistry (n = 112, 38.6%) students in three Russell Group universities in England. The majority of participants (n = 115, 43.1%) were between 18 and 19 years old. Data were collected and analysed using a structural equation model and multigroup analysis. The study findings revealed that MPSS, GSE, and SI had a positive impact on students’ SB, while CSSQ and SVS-4 had a negative impact on students’ SB. The findings revealed that the influence of MPSS on SB and the effect of GSE on SI were found to be statistically significant among female, male, and non-binary students, as well as across A-level, undergraduate, master’s, and Ph.D. levels.